Reverse Transcription Polymerase Chain Reaction (RT-PCR) as an influenza diagnostic test among children in Yogyakarta - Eva Musdalifah; M. Juffrie; Purnomo S; Amalia Amalia (Indonesian Pediatric Society, 2008)
Background Influenza virus type A, especially H5Nl subtype oravian influenza, is a highly pathogenic agent that causes epidemicin the world with high mortality. Most cases are preschool andschool children. Anti-viral drug is effective when given at earlyphase. The gold standard for the diagnosis of influenza is viralculture, which takes 2 to 10 days. A rapid and accurate diagnostictest is needed to control further viral infection.Objective To determine the accuracy of RT-PCR as a diagnostictest for children with influenza compared with viral culture.Methods A cross-sectional study was conducted in primary healthcares of Jetis I, Godean I, II and Dr Sardjito Hospital Yogyakartabetween January 2005 and May 2007. The specimens, taken bytrained health personnel, were collected from both anterior naresand throat of children aged from birth to 14 years who met theeligibility criteria, then were stored in a frozen extraction tubeand sent to Jakarta for RT-PCR and viral culture as the goldstandard.Results There were 34 7 children enrolled in this study. Influenzainfection was confirmed in 63 children (18.2%). There were 24children with H3N2 subtype of influenza virus, 13 children withHINI subtype, and one child with H5Nl subtype. The sensitivity,specificity, positive and negative predictive value, positive andnegative likelihood ratio of RT-PCR test were 89%, 90%, 67%,97%, 9, 3, 0, and 12 respectively.Conclusions RT-PCR is accurate enough as influenza diagnostictest in children.